Effect of different running protocols on bone morphology and microarchitecture of the forelimbs in a male Wistar rat model. - Andy Xavier; Céline Bourzac; Morad Bensidhoum; Catherine Mura; Hugues Portier; Stéphane Pallu (PLoS ONE)
Background It is accepted that the metabolic response of bone tissue depends on the intensity of the mechanical loads, but also on the type and frequency of stress applied to it. Physical exercise such as running involves stresses which, under certain conditions, have been shown to have the best osteogenic effects. However, at high intensity, it can be deleterious for bone tissue. Consequently, there is no clear consensus as to which running modality would have the best osteogenic effects. Aim Our objective was to compare the effects of three running modalities on morphological and micro-architectural parameters on forelimb bones. Methods Forty male Wistar rats were randomly divided into four groups: high intensity interval training (HIIT), continuous running, combined running ((alternating HIIT and continuous modalities) and sedentary (control). The morphometry, trabecular microarchitecture and cortical porosity of the ulna, radius and humerus were analyzed using micro-tomography. Results All three running modalities resulted in bone adaptation, with an increase in the diaphyseal diameter of all three bones. The combined running protocol had positive effects on the trabecular thickness in the distal ulna. The HIIT protocol resulted in an increase in both medio-lateral diameter and cortical bone area over total area (Ct.Ar/Tt.Ar) at the ulnar shaft compared with sedentary condition. Moreover, the HIIT protocol decreased the mean surface area of the medulla (Ma.Ar) according to sedentary condition at the ulnar shaft. Conclusion This study has shown that HIIT resulted in a decrease in trabecular bone fraction in favor of cortical bone area at the ulna.